Analysis of optical frequency domain reflectometry (OFDR) interferometer for passive optical network (PON) monitoring / Faris Aiman Asha’ari, Nani Fadzlina Naim, and A. Ashrif A. Bakar - Asha’ari, Faris Aiman; Naim, Nani Fadzlina; A. Bakar, A. Ashrif (Universiti Teknologi MARA, 2019)
This paper presents the design of Optical Frequency Domain Reflectometry (OFDR) interferometer for Passive Optical Network (PON). This monitoring system is anticipated for Pointto-Multipoint (P2MP) network monitoring. The interferometer is designed based on Fiber Bragg Grating (FBG) which are placed in every distribution fibers and one FBG is placed at the receiver. The FBGs reflections spectra will produce beat frequencies which will distinguish the branches. By comparing the Distributed Feedback (DFB) Laser and Light Emitting Diode (LED) at 1530nm centre wavelength as the monitoring source, the spectra produced by both monitoring sources were observed in the RF spectrum analyzer. It is found that the system is capable to monitor up to 64 customers with the downstream power received of -24.5 dBm and 0.08 dB of excess power margin.